From Oasis Archipelago to Pioneering Eldorado in Algeria's Sahara - F. Amichi; S. Bouarfa; M. Kuper; P. Caron (Irrigation and Drainage, 2020)
Since the 1980s, the Biskra region in Algeria's Sahara has undergone rapid agricultural change leading to territorial transformation. Horticultural production under greenhouses, associated with a rapid expansion of date palm plantations, has led to a tangible agricultural boom that is constantly pushing the boundaries of agricultural production and constitutes a true pioneering fringe. To understand the pioneering logics at work, we propose to study the pioneer fringe through three fronts, namely land, water and infrastructure. First, we analyse each front separately in order to understand its logic. In a second step, through three illustrations, we show how these fronts interpenetrate, accelerate one another or, on the contrary, constrain the pioneer fringe. The analysis of the advance of the pioneering fringe has shown that it results from the interweaving of the three main fronts and each of these combines both the actions of the state and private initiative. © 2018 John Wiley & Sons, Ltd.